2015
DOI: 10.1194/jlr.m055624
|View full text |Cite
|
Sign up to set email alerts
|

Top-down lipidomics of low density lipoprotein reveal altered lipid profiles in advanced chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a serious and increasingly common condition ( 1 ). Patients with CKD have a greatly increased risk of CVD, which represents the most common cause of mortality and morbidity in these patients, to the extent that CKD is considered an independent risk factor for CVD ( 2, 3 ). In CKD, many conventional risk factors for CVD are prevalent, including hypertension, dyslipidemia, and insulin resistance. Underlying conditions that are typical of CVD also occur, such as heightened infl amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 52 publications
6
53
0
Order By: Relevance
“…In other studies plasma phosphatidylcholines and ceramides were shown to be substantially reduced in chronic renal disease (40). When we examined which lipids were differentially altered by the dairy and soy meals, we observed that alkylphosphatidylcholine, alkenylphosphatidylcholine, and alkylphosphatidylethanolamine showed slight increases after the dairy meal but a decrease after the soy meal.…”
Section: Discussionmentioning
confidence: 90%
“…In other studies plasma phosphatidylcholines and ceramides were shown to be substantially reduced in chronic renal disease (40). When we examined which lipids were differentially altered by the dairy and soy meals, we observed that alkylphosphatidylcholine, alkenylphosphatidylcholine, and alkylphosphatidylethanolamine showed slight increases after the dairy meal but a decrease after the soy meal.…”
Section: Discussionmentioning
confidence: 90%
“…In a recently published report, Reis et al, have compared the lipid signature of LDL in patients at advanced stage of CKD (stage 4 and 5) with the control group using the Liquid Chromatography/Mass Spectrometry (LC/MS)-based lipidomics approach. 18 To our knowledge there is no study in CKD aimed at identification of lipid signature predictive of incident ESKD at early stages of CKD. Therefore this study examines the systematic identification of prognostic serum lipid metabolites at CKD stage 2 and 3 to predict progression to ESKD using LC/MS based lipidomics in the Chronic Renal Insufficiency Cohort (CRIC) patient population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fatty acids, the same study found that reduction in eGFR levels is also linked to an increase in LPC (24: 1) and a decrease in PC (20: 2/24: 1) levels, which are both glycerophospholipids [39]. Reis et al[40] stated that phosphadylcholine, plasmenyl ethanolamine, sulfatide, ceramide, and cholesterol sulfate levels can decrease in the LDL cholesterol structure of CKD patients, whereas triacylglyceride and N-acyltaurine levels can increase. Therefore, these changes could cause atherosclerotic plaque formation even though the inflammatory markers and oxidized LDL cholesterol levels are normal.…”
Section: Lipidomics In Ckdmentioning
confidence: 99%